Model for Insurance Fraud Risk Assessment and Prevention - Asenov, Emil (UNWE Yearbook, 2017)
This article critically examines insurance frauds in terms of the risk they create and the significant losses they bring to the insurance industry. A comparative analysis of the classification of insurance frauds in the legal systems of many developed countries has been conducted. A model for risk assessment and the prevention of insurance frauds is presented. In the suggested model the overall risk assessment is achieved by the evaluation of risk elements – probability, exposure (frequency) and results. The possibilities for the practical application of the model of insurance frauds assessment and prevention in the insurance organizations practices have been outlined.
Keywords: Insurance frauds; Legal classification of insurance frauds; Insurance fraud risk assessment; Insurance fraud risk prevention